PENGARUH DUE PROFESSIONAL CARE, INDEPENDENSI, TIME BUDGET PRESSURE, DAN AUDIT FEE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA MEDAN - Zain, Jenny; Putri, Arie Pratania; Tarigan, Aremi Evanta; Novita T, Siti; Voltra, Jhon (Aksara Public, 2019)
This research studies about the influence of due professional care, independency, time budget pressure, and audit fee to the audit quality. At 8 Accountant Public Firm in Medan. This study used simple random sampling. The data were collected through questions survey methods. The results of the study indicate that simultaneous due professional care, independency, time budget pressure, and audit fee had a significant effect to the audit quality. In the partiality due professional care, independency, and audit fee had a positive effect and significant to the audit quality. While time budget pressure had a negative effect and significant to the audit quality.